Effect of Different Water-to-powder Ratios on the Solubility and Microhardness of Calcium-Enriched Mixture Cement - Sadat Shojaee, Nooshin; Adl, Alireza; Jafarpour, Dana; Sobhnamayan, Fereshteh (Iranian Endodontic Journal, 2019)
Introduction: The aim of this study was to evaluate the effect of different water-to-powder (WP) proportions on the microhardness and water solubility of calcium-enriched mixture (CEM) cement. Methods and Materials: One gram of CEM cement powder was mixed with 0.33 mL, 0.4 mL or 0.5 mL CEM liquid. For water solubility, a total of 60 specimens were prepared (n=20 per each ratio) in the disk-shaped stainless-steel molds with a height of 1.5±0.1 mm and internal diameter of 10.0±0.1 mm. The specimens of each WP ratio were randomly divided into two subgroups: half (n=10) were immersed for one day and the other half (n=10), were kept for 21 days in distilled water. The solubility was calculated as a percentage of the weight loss. To measure microhardness, a total of 30 samples were prepared (10 per each ratio, n=10). The mixtures were transferred to metallic cylindrical molds with internal dimensions of 6±0.1 mm height and 4±0.1 mm diameters. After 4 days the specimens were subjected to Vicker's test. The data were analyzed using two-way ANOVA and post-hoc Tukey’s tests at a significance level of 0.05. Results: The 0.33 WP ratio showed significantly greater microhardness value (25.98±2.77) compared to 0.4 and 0.5 proportions (P=0.004 and P<0.001 respectively). Significant differences were observed between water solubility values of different WP ratios at both time intervals (P<0.001). At both time intervals, 0.33 and 0.5 WP ratios exhibited the lowest and highest solubility, respectively. Conclusion: According to the results of this in vitro study, higher WP ratios result in lower microhardness and higher water solubility of the CEM cement. Therefore, the 0.33 WP ratio would be the ideal proportion. Keywords:Calcium-Enriched Mixture; CEM Cement; Microhardness; Solubility; Water-to-powder Ratio